JOB SATISFACTION AND DEVELOPMENT OF A HUMAN RESOURCE MANAGEMENT POLICY - Ali Sarabi Asiabar; Mahmoud Biglar; Pezhman Atefi Manesh; Shandiz Moslehi (Strategii Manageriale, 2013)
Job satisfaction is a key factor influencing effectiveness, efficiency and also productivity. The objective of this study was to investigate Iran University of Medical Sciences employees’ job satisfaction and prioritize the criteria for improving job satisfaction. Data were gathered on all units of hospitals, primary health centers, health facilities and colleges of Iran University of Medical Sciences by a questionnaire. By using the Spearman test we found a negative correlation between overall job satisfaction and age (p = -0.157), and between overall job satisfaction and job experience (p = -0.325). Job dissatisfaction was found in 2 scopes: career development and compensation and benefits. This study gives the insight to develop the job satisfaction by calculating weights of each factor and prioritizing them. This model can be used by other countries.